Craniofacial Implants Success in Facial Rehabilitation - Goiato, Marcelo Coelho [UNESP]; Santos, Daniela Micheline dos [UNESP]; Dekon, Stefan Fiuza de Carvalho [UNESP]; Pellizzer, Eduardo Piza [UNESP]; Santiago, Joel Ferreira; Moreno, Amalia (Lippincott Williams & Wilkins, 2011)
The use of craniofacial implants is an effective treatment for patients with deformities, burns, and cancer sequelae. The sites with the most successful implants are the auricular, nasal, and orbital regions. Furthermore, other factors can affect the implant longevity such as irradiated area, surgical technique, bone quality and quantity, macrostructure and microstructure of the implant, maintenance, and systemic factors.
Keywords: Rehabilitation; osseointegrated implants; maxillofacial prosthesis